PARTICIPAÇÃO NO PROCESSO QUE ANTECEDEU A IFRS 16 - LOCAÇÕES: UM CONTRIBUTO PARA O ESTUDO DO LOBBYING - Teresa Monteiro; Lopes, A.I. (XIX Congreso AECA, 2017)
In 2019 will be effective the IFRS 16, Leasing, ten years after its first inclusion in the International Accounting Standards Board (IASB) agenda. The present paper examines the 645 comment letters submitted by a larger range of stakeholders to comment on the proposal on the changes of the effect of leasing in financial statements. Findings suggest that the amount of comment letters submitted is associated with the annual volume of leases by country, the existence of leases’ contracts by company and the G4+1 membership, although no association exists with UE membership. Results seem to also show that the preparers are the one, in average, with a lower percentage of agreement answers when compared with the other stakeholders.